2022
DOI: 10.1021/acsomega.1c06154
|View full text |Cite
|
Sign up to set email alerts
|

Improving the GaN Growth Rate by Optimizing the Nutrient Basket Geometry in an Ammonothermal System Based on Numerical Simulation

Abstract: The low growth rate of bulk gallium nitride (GaN) when using the ammonothermal method is improved herein by optimizing the nutrient geometry. A numerical model considering the dissolution and crystallization process is developed. Heater powers are employed as thermal boundary conditions to match the real ammonothermal system. The flow field, thermal field, and mass concentration field in the autoclave are calculated with or without a central hole in the nutrient basket. Numerical results show that the mass tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The structure and geometric size of the autoclave are shown in Figure 1. According to our previous research [24], a nutrient basket with a central hole is beneficial for the improvement of the growth rate. Thus, the optimized model is used in this paper.…”
Section: Geometric Model Of the Ammonothermal Systemmentioning
confidence: 97%
See 1 more Smart Citation
“…The structure and geometric size of the autoclave are shown in Figure 1. According to our previous research [24], a nutrient basket with a central hole is beneficial for the improvement of the growth rate. Thus, the optimized model is used in this paper.…”
Section: Geometric Model Of the Ammonothermal Systemmentioning
confidence: 97%
“…Multi-physics fields and their couplings are calculated in the numerical simulation, including flow, heat transfer, and diluted mass transport. The corresponding differential equations can be acquired from [24]. Bossinesq approximation is employed for the calculation of natural convection.…”
Section: Governing Equationsmentioning
confidence: 99%
“…Since then, at least two noteworthy papers were published. In the first, Han et al report on a crucible design that is indicated to improve convective flow and gallium uptake in computational fluid dynamics (CFD) simulations [39]. Adding a hole to the center of the basket containing the GaN feedstock, they predict improved nutrient dissolution and transport of gallium-containing species to the growth zone.…”
Section: In Situ Measurements Of Ammonothermal Growthmentioning
confidence: 99%